Entrepreneurship Assistance to Increase Omak Kopi’s MSME Income In The New Normal Era: Article - Christina Heti Tri Rahmawati; Rubiyatno Rubiyatno; Theodorus Sutadi; Trisnawati Rahayu (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2022)
Purpose This community service raises the problems faced by a coffee shop business called Omak Kopi. Based on interviews, there are several problems experienced by the owners of these Micro, Small and Medium Enterprises (MSMEs), namely the management of business legality and product marketing. Methods - The method used in this community service activity is to provide understanding and awareness to MSME actors about the importance of having business legality, providing entrepreneurial assistance in the form of business models, and providing product marketing assistance through social media. Result and discussions - The results of community service activities for MSME Omak Kopi include: (1) This MSME has business legality: (2) This MSME has a business capital canvas to develop a business; and (5) these MSMEs have business signage and use social media Whatsapp and Instagram as well as online food delivery service platforms through Grab Food and Go Food to increase product marketing. Conclusion - The implication of this community service activity is that it is hoped that the existence of entrepreneurship assistance can facilitate Omak Kopi SMEs to manage patent rights, business development and increase income and business continuity, especially in the new normal era. Keywords: Business Legality, Entrepreneurship, Marketing, Income